2017
DOI: 10.11646/zootaxa.4258.6.2
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia

Abstract: A new species of Asian rock gecko, genus Cnemaspis, is described from Padawan, western Sarawak, Malaysian Borneo. The new species forms a clade with C. paripari and C. nigridia of the C. nigridia group in a mitochondrial DNA phylogeny and is similar to them morphologically in some characters such as caudal scalation. It differs from the other Asian Cnemaspis species in its unique combination of snout-vent length (up to 62.7 mm), 4-9 precloacal pores in males, keeled subcaudals with an enlarged, smooth, median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 797 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…We compared the specimens to specimens and descriptions of all congeners (Appendix 1). Some of the information on character states and their distribution in other Southeast Asian species were obtained from Grismer et al (2014a), Amarasinghe et al (2015), Iskandar et al (2017), and Kurita et al (2017). All type specimens were deposited in the Museum Zoologicum Bogoriense (MZB), Indonesian Institute of Sciences (LIPI), Cibinong, Bogor, Indonesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the specimens to specimens and descriptions of all congeners (Appendix 1). Some of the information on character states and their distribution in other Southeast Asian species were obtained from Grismer et al (2014a), Amarasinghe et al (2015), Iskandar et al (2017), and Kurita et al (2017). All type specimens were deposited in the Museum Zoologicum Bogoriense (MZB), Indonesian Institute of Sciences (LIPI), Cibinong, Bogor, Indonesia.…”
Section: Methodsmentioning
confidence: 99%
“…In Southeast Asia, Cnemaspis ranges from southern Laos in the north, southward through Vietnam, Cambodia, and Thailand, and the Thai-Malay Peninsula, eastward to Borneo through the Seribuat, Anambas and Natuna archipelagoes, and southward to Sumatra and the Mentawai Archipelago (de Rooij, 1915;Grismer et al 2010Grismer et al , 2013Grismer et al , 2014aWood et al 2013;Amarasinghe et al 2015;Iskandar et al 2017). The genus Cnemaspis Strauch currently includes 135 recognized species (Uetz et al 2017), five of which are present on Borneo: C. kendallii (Gray, 1845), C. nigridia (Smith, 1925), C. dringi , C. paripari Grismer & Chan, 2009 and C. leucura Kurita, Nishikawa, Matsui & Hikida, 2017. Several new species have been described from Indonesia in recent years (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, competition from other geckos, including other sympatric Cnemaspis congeners, might also led to the temporal niche partition, leading to the somewhat inconsistent relationship between diel niche and sympatry between Cnemaspis and Cyrtodactylus species. For example, it has been reported that Cnemaspis congeners could have sympatric distribution and temporal niche partition (C. kendallii versus C. nigridia, C. leucura versus C. kendallii and C. monachorum versus C. roticanai 12,27,28 ). Furthermore, competition pressure might also come from nocturnal geckos other than Cyrtodactylus species, as they are abundant in Southeast Asia 29 .…”
Section: Discussion Temporal Niche Responses To Competition and Envirmentioning
confidence: 99%
“…In spite of the contribution to long‐term population shrinkage, habitat specialization may also play a critical role in facilitating differentiation among populations. Among a total of 55 species in Cnemaspis , there are more than 30 rocky habitat specialists, most of which have restricted distributions (Grismer et al, ; Grismer, Wood, Quah et al, ; Grismer, Wood, Tri et al, ; Kurita, Nishikawa, Matsui, & Hikida, ; Wood et al, ). In addition to Cnemaspis species, several Cyrtodactylus geckos also occupy these small hills in the Mekong Delta; and all show extremely limited distributional ranges (Grismer, Wood, Quah et al, ; Grismer, Wood, Tri et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…in Cnemaspis, there are more than 30 rocky habitat specialists, most of which have restricted distributions (Grismer et al, 2014;Grismer, Wood, Quah et al, 2015;Grismer, Wood, Tri et al, 2015;Kurita, Nishikawa, Matsui, & Hikida, 2017;Wood et al, 2017). In addition to Cnemaspis species, several Cyrtodactylus geckos also occupy these small hills in the Mekong Delta; and all show extremely limited distributional ranges (Grismer, Wood, Quah et al, 2015;Grismer, Wood, Tri et al, 2015).…”
Section: Strong Isolation Has Facilitated Speciation Among Habitat mentioning
confidence: 99%